Practitioner-Customizable Clinical Information Systems: A Case Study to Ground Further Research and Development Opportunities. Issue 3 (2010) - Morrison, Cecily; Blackwell, Alan F.; Vuylsteke, Alain
Abstract : The uptake of electronic records and information technology support in intensive care medicine has been slower than many people predicted. One of the engineering challenges to overcome has been the subtle, but important, variation in clinical practice in different units. A relatively recent innovation that addresses this challenge is practitioner-customizable clinical information systems, allowing clinicians wide scope in adjusting their systems to suit their clinical practice. However, these systems present a significant design challenge, not only of added technical complexity, but in providing tools that support clinicians in doing many of the tasks of a software engineer. This paper reviews the use of a commercially available clinical information system that is intended to be practitioner-customizable, and considers the further design and development of tools to support healthcare practitioners doing end-user customization on their own clinical information systems.